EVALUASI SISTEM ONLINE PUBLIC ACCESS CATALOG PERPUSTAKAAN UMUM DAERAH PROVINSI DKI JAKARTA, CIKINI - Junaedi, Jusa (Journal of Documentation and Information Science, 2017)
This article will try to analyze and to evaluate the Online Public Access Catalog that is available in Perpustakaan Umum Daerah Provinsi DKI Jakarta, Cikini. This research uses qualitative approach with the method of descriptive case study. The data collection is accumulated through participative observations, in-depth interview with selected informants, and analysis on supporting documents. The result of this research shows that the Online Public Access Catalog that is owned by Perpustakaan Umum Daerah Provinsi DKI Jakarta, Cikini has several problems. It can be seen from the limited choices of searching mode, the usage of INDOMARC indicator codes in describing information bibliography of collection that often cannot be comprehended by public, the search results from the local library?s collections that are mixed with other library?s collections, to collection?s status and filter system that is not available